2001
DOI: 10.1542/peds.107.6.e100
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Improper Vaccine Storage and Handling in Private Provider Offices

Abstract: ABSTRACT. Context. Preventing loss of vaccine potency during storage and handling is increasingly important as new, more expensive vaccines are introduced, in at least 1 case requiring a different approach to storage. Little information is available about the extent to which staff in private physicians' offices meet quality assurance needs for vaccines or have the necessary equipment. Although the National Immunization Program at the Centers for Disease Control and Prevention (CDC) in 1997 developed a draft ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 4 publications
3
42
0
6
Order By: Relevance
“…Predictors of vaccine handling and storage practices were found to be utilization of vaccine handling and storage guideline, exposure to formal training on vaccine management, and level of knowledge of vaccine handling and storage. Awareness of vaccine handling and storage guideline was not a significant predictor of vaccine handling and storage practices 11 . This study brings to the forefront several challenges to effective cold chain management such as highly unstable power supply as also reported by other studies on cold chain management in developing countries 1,3 .…”
Section: Discussionmentioning
confidence: 81%
“…Predictors of vaccine handling and storage practices were found to be utilization of vaccine handling and storage guideline, exposure to formal training on vaccine management, and level of knowledge of vaccine handling and storage. Awareness of vaccine handling and storage guideline was not a significant predictor of vaccine handling and storage practices 11 . This study brings to the forefront several challenges to effective cold chain management such as highly unstable power supply as also reported by other studies on cold chain management in developing countries 1,3 .…”
Section: Discussionmentioning
confidence: 81%
“…b Additional data was acquired through e-mail correspondence with the author to resolve questions about the reported data such as what temperatures were measured during transport versus storage legs of cold chain assessment [13,15] how many unacceptable temperature readings were in the freezing range [32] or how many refrigerators were included per physician practice [41].…”
Section: Identified Studiesmentioning
confidence: 99%
“…1 However, practices that expose vaccines to sub-zero temperatures are widespread in both developed and developing countries at all health system levels. [2][3][4][5][6][7][8][9][10][11] The most recent systematic literature review of vaccine freezing practices showed that accidental freezing occurs across all parts of the cold chain. 12 Between 14% and 35% of refrigerators or transport shipments were found to have exposed vaccines to freezing temperatures, while in studies that examined all segments of the distribution chain, between 75% and 100% of the vaccine shipments were exposed.…”
Section: Introductionmentioning
confidence: 99%